مفتی محمد رفیع عثمانؒی کا تعارف اور ان کی دینی خدمات کا جائزہ: Introduction of Mufti Muhammad Rafiee Usmani (R.A) and Review of his Religious Services - Muhammad Tahir Hussain; Arslan Arif; Hafiz Mudasser Riaz (AL-IDRAK JOURNAL, 2023)
The introduction of Mufti Muhammad Usmani (1936-2022) is mentioned in this dissertation. He was a man with multidimensional personality. Being a religious scholar he was successful teacher and administrater and had qualities such as an antitheologian, scholar and writer, Muhadis as well. He was syndicate member of Karachi Jamiyah and administrating member of Wafaq Al Madaris Al Arbia’s majlish and also served as vice president. The author 32 books while serving as a teacher in Jamiyah Dar Ul Aloom Karachi. This thesis is about his introduction also highlight his services